Postural pattern recognition in children with unilateral cerebral palsy - Domagalska-Szopa M; Szopa A (Dove Medical Press, 2014)
Małgorzata Domagalska-Szopa, Andrzej Szopa School of Health Sciences, Medical University of Silesia, Katowice, Poland Background: Several different strategies for maintaining upright standing posture in children with cerebral palsy (CP) were observed. Purpose: The purpose of the present study was to define two different postural patterns in children with unilateral CP, using moiré topography (MT) parameters. Additionally, another focus of this article was to outline some implications for managing physiotherapy in children with hemiplegia. Patients and methods: The study included 45 outpatients with unilateral CP. MT examinations were performed using a CQ Elektronik System device. In addition, a weight distribution analysis on the base of support between unaffected and affected body sides was performed simultaneously. A force plate pressure distribution measurement system (PDM-S) with Foot Print software was used for these measurements. Results: The cluster analysis revealed four groups: cluster 1 (n=19; 42.22%); cluster 2 (n=7; 15.56%); cluster 3 (n=9; 20.00%); and cluster 4 (n=10; 22.22%). Conclusion: Based on the MT parameters (extracted using a data reduction technique), two postural patterns were described: 1) the pro-gravitational postural pattern; and 2) the anti-gravitational pattern. Keywords: deviation of body posture, strategy of compensation, moiré topography examinations, cluster analysis